EZ online printing services - Nursyahirman, A. Rahman (2018)
In this era, a lot of advancement in technology and websites already created to help people in their life. EZ Online Printing Services (EZOPS) is developed for the students in University Malaysia Pahang (UMP). Not just that, it is also can be use by the staffs and worker of University Malaysia Pahang (UMP). In the meantime, the printing shops still using the old system which student needs to queue and wait for a long time in the shops but not now. This will cause the printing shop to be crowded especially in the peak hour. Besides, they only needs to send their documents through the system and wait for it to be printed. As the result, students can use their time to studies or even hanging out with their friends doing outdoor activities. The result is important to achieve the objectives of the project.